DISFEMISME DALAM PERSPEKTIF SEMANTIK, SOSIOLINGUISTIK, DAN ANALISIS WACANA - Laili, Elisa Nurul (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2017)
Dysphemism is an expression with connotations that are offensive either about the denotatum or the audience. It is used to talk about one’s opponents, things one wishes to show disapproval of, and things one wishes to be seen to downgrade. The topic of dysphemism is crucial to investigate because dysphemism is the infraction of the rules of politeness that deals with the matters of face and face effects.This research uses descriptive qualitative method. The approach used in this research is library research. Data taken from taking notes and observation.This article is written to explain dysphemism in the perspective of Semantics, Sociolinguistics, and Discourse Analysis.